Russia Economic Report, May 2018 : Modest Growth Ahead - World Bank Group (World Bank, Washington, DC, 2018)
Global growth continued its 2017 momentum in early 2018. Global growth reached a stronger than- expected 3 percent in 2017 — a notable recovery from a post-crisis low of 2.4 percent in 2016. It is currently expected to peak at 3.1 percent in 2018. Recoveries in investment, manufacturing, and trade continue as commodity-exporting developing economies benefit from firming commodity prices (Figure 1a). The improvement reflects a broad-based recovery in advanced economies, robust growth in commodity-importing Emerging Markets and Developing Economies (EMDEs), and an ongoing rebound in commodity exporters. Growth in China – and important trading partner for Russia – is expected to continue its gradual slowdown in 2018 following a stronger than-expected 6.9 percent in 2017.